2011
DOI: 10.1017/s0003055410000584
|View full text |Cite
|
Sign up to set email alerts
|

Do Natural Resources Fuel Authoritarianism? A Reappraisal of the Resource Curse

Abstract: A large body of scholarship finds a negative relationship between natural resources and democracy. Extant cross-country regressions, however, assume random effects and are run on panel datasets with relatively short time dimensions. Because natural resource reliance is not an exogenous variable, this is not an effective strategy for uncovering causal relationships. Numerous sources of bias may be driving the results, the most serious of which is omitted variable bias induced by unobserved country-specific and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
451
1
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(472 citation statements)
references
References 34 publications
12
451
1
8
Order By: Relevance
“…Using cross-country regressions, Sachs and Warner (2001) and other studies have found empirical evidence for a "resource curse" -namely, slower economic growth for resource rich countries versus resource poor countries. Subsequent studies using different measures of resource "richness" and panel data have found either insignificant or positive effects of natural resource abundance (Brunnschweiler and Bulte (2008), Alexeev andConrad (2009), Haber andMenaldo (2011)). While empirical results are mixed, a key outcome of this literature is that the existence of the resource curse is conditional on country-specific factors such as the quality of institutions and governance, as well as the type of commodity specialization.…”
mentioning
confidence: 99%
“…Using cross-country regressions, Sachs and Warner (2001) and other studies have found empirical evidence for a "resource curse" -namely, slower economic growth for resource rich countries versus resource poor countries. Subsequent studies using different measures of resource "richness" and panel data have found either insignificant or positive effects of natural resource abundance (Brunnschweiler and Bulte (2008), Alexeev andConrad (2009), Haber andMenaldo (2011)). While empirical results are mixed, a key outcome of this literature is that the existence of the resource curse is conditional on country-specific factors such as the quality of institutions and governance, as well as the type of commodity specialization.…”
mentioning
confidence: 99%
“…Smith E.g. Acemoglu et al 2008;Boix 2003;Dunning 2008;Epstein et al 2006;Goldberg, Mvukiyehe and Wibbels 2008;Haber and Menaldo 2011;Jensen and Wantchekon 2004;Ramsay 2011. 10 Morrison 2009. models the likelihood of revolutionary onsets and the response of the government as a function of "unearned income," which includes revenue from oil as well as foreign aid.…”
mentioning
confidence: 99%
“…One way of moving beyond the correlations would be to run multivariate regressions on large numbers of countries and variables, in order to narrow down the causal relationships. This is the type of exercise Haber and Menaldo (2011) did in their much-quoted article arguing that natural resource wealth does not necessarily lead to authoritarianism. However, such analyses are not unproblematic (see Papaioannou and Siourounis 2008, 366, 370;Andersen and Ross 2014).…”
Section: Polycentricity and Resource Management: A First Glance At Thmentioning
confidence: 99%
“…Wiens (2014, 198) creates a formal model to show that resource revenue makes it difficult to develop strong institutions. Haber and Menaldo (2011) launch a critique of this literature, and of the work of Ross in particular, arguing that most of the findings are due to methodological weaknesses in the regressions applied. For more a detailed overview of this literature, see Boschini et al (2013, 22).…”
Section: Notesmentioning
confidence: 99%